(untitled) (Journal of Basic and Applied Research in Biomedicine, 2024)
Nanomaterials have revolutionized various fields of medicine, providing innovative solutions for drug delivery, diagnostics, vaccines, and regenerative therapies. The aim of this review is to explore the diverse applications of nanomaterials in medicine, highlighting their potential to enhance treatment efficacy, improve patient outcomes, and address complex medical challenges. Through successful applications like Doxil and Abraxane, nanotechnology has demonstrated its ability to improve targeted drug delivery, while lipid nanoparticles have played a pivotal role in the development of mRNA vaccines for COVID-19. Nanomaterials offer unique advantages, such as their small size, tunable surface properties, and the ability to cross biological barriers, which enable precision therapies and improved diagnostic sensitivity. However, this review also addresses the challenges associated with nanomaterials, including safety concerns, potential toxicity, long-term biodegradability, and the regulatory hurdles that must be overcome for clinical translation. As researchers work to develop biocompatible and biodegradable materials, new opportunities arise in personalized medicine, stimuli-responsive nanomaterials, and theranostics that combine diagnosis and therapy into a single platform. In conclusion, while nanotechnology in medicine offers immense potential for future medical innovations, addressing safety and regulatory challenges will be crucial for the broader adoption of nanomaterials in clinical practice. This review emphasizes the need for continued research and development to realize the full potential of nanomedicine in improving healthcare outcomes globally.